Control Characteristics Analysis of Multi-Section Morphing Wing Based on Centroid Self-Trimming - Hang Ma; Zhongbin Zhou; Dingshan Zhang (IEEE Access)
Based on the research on the sweep angle change of the elbow and hand wing sections during the flight of large birds, this paper proposes a multi-section variable-sweep wing structure suitable for large-scale UAVs. The characteristics of multi-section variable-sweep wing are explored from the perspective of morphing controller design. This research selects stable roll and pitching motion to investigate the feasibility and effectiveness of using the asymmetric change of sweep angle as the control input and using the reverse collaborative morphing of the inner and outer wing sections to achieve centroid self-trimming. The computational analysis results show: 1) The asymmetry morphing of the sweep angle can significantly improve the maneuvering control performance of the UAV with a large lift coefficient. 2) The overall control efficiency of the UAV can be effectively improved by increasing the deflection rate of the sweep angle and the system parameters of the main controller and supervisory controller. 3) Increasing the feedback value of the integral term of the PI compensator in the inner loop can reduce the oscillation degree of the inner loop system in tracking the target signal when the Mach number is large, and improve the tracking accuracy of the inner loop system. 4) Increasing the wingspan ratio of the inner wing section can reduce the elevator deflection angle required to track the target pitch signal during the morphing process. This research provides a reference for the practical application of multi-section variable-sweep wings.